PREFERENSI MAHASISWA IPB TERHADAP MATA KULIAH METODE STATISTIKA MENGGUNAKAN ANALISIS KONJOIN - Eka Dewi Pertiwi; Utami Dyah Syafitri; Yenni Angraini (FORUM STATISTIKA DAN KOMPUTASI, 2011)
Statistical method is one of the interdepth courses in Bogor Agricultural University (BAU) therefore, it is necessary to conduct an evaluation in order to know the student's preference towards Statistics Methods course. Conjoint analysis is an analysis that can be used to determine the preference of students on teaching methods of Statistical Methods course. The combination of teaching methods are made using fractional factorial in which the level of factor determined was based on preliminary survey. Sampling techniques that has been used was multistage sampling of students who had took the Statistical Methods course in 2009/2010. Based on conjoint analysis, the module, the number of students, and the time period of lectures are the top three choices. The students tend to prefer materials that are appropriate with their major, modules that are well structured, a communicative lecturer, students as a teacher in review session, the number of student which is less than 50 students per class, and the time period of lecture is between 7-12 am. Keywords : statistical methods, preferences, conjoint analysis.